2016
DOI: 10.1016/j.jaad.2016.04.028
|View full text |Cite
|
Sign up to set email alerts
|

ATX-101 for reduction of submental fat: A phase III randomized controlled trial

Abstract: _ Die Haut ist bekanntlich der Spiegel der Seele. So gesehen düre es mit dem seelischen Benden in der Bevölkerung sehr schlecht bestellt sein: Gaubt man den Dermatologen, so gibt es kaum noch jemanden, bei dem sich die Seele nicht in Form von Rötungen, Juckreiz, Bläschen oder Flecken an der Haut zumindest ge-legentlich bemerkbar macht. Und manch einer kratzt sich sogar, bevor es juckt. Angesichts dessen hat sich in den letz-ten Jahren in der Dermatologie ein neu-es Teilgebiet etabliert: die Psychoderma-tologie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
99
0
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(114 citation statements)
references
References 10 publications
5
99
0
10
Order By: Relevance
“…Based on this study, DC was suggested to be the principal component acting on the reduction of adipose tissue [12]. ATX-101, an injectable form of DC, was recently approved for submental fat reduction [17]. Consistent with this, our present study also showed that DC has a slightly stronger effect on the decrease of 3T3L1 preadipocyte viability (Fig 3A).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Based on this study, DC was suggested to be the principal component acting on the reduction of adipose tissue [12]. ATX-101, an injectable form of DC, was recently approved for submental fat reduction [17]. Consistent with this, our present study also showed that DC has a slightly stronger effect on the decrease of 3T3L1 preadipocyte viability (Fig 3A).…”
Section: Discussionsupporting
confidence: 88%
“…However, safety is the most important criterion for application as a therapeutic agent. DC injections have been associated with many adverse events including pain, edema, numbness, and swelling, although these were transient and restricted to the injected sites [17]. Furthermore, patients who received DC injections complained of pain more so than those treated with the PPC/DC formula [13].…”
Section: Discussionmentioning
confidence: 99%
“…[2528, 3134] In 2015, sodium deoxycholate (SD) was approved by the FDA to reduce the unwanted submental fat, a very different compound from those previously available. [3537] SD acts like a detergent, causing adipolysis (or adipocytolysis) when injected directly into the area with extra fat tissue. [36, 38] SD lyses the adipocyte’s membrane, which is deficient in cell associated proteins, resulting in necrosis.…”
Section: Introductionmentioning
confidence: 99%
“…Several phase III, multicenter, randomized, placebo‐controlled, double‐blinded clinical trials with >1,700 patients have demonstrated the dose‐dependent efficacy of ATX‐101 (Table ). Adverse events were very common but transient and localized to the treatment area such as injection pain, swelling, bruising, numbness, and induration (Ascher et al, ; Dunican & Patel, ; Humphrey et al, ; Jones, Carruthers, et al, ; Rzany et al, ).…”
Section: Injection Lipolysis With Atx‐101mentioning
confidence: 99%
“…ATX-101 for submental contouring; randomized, placebo-controlled trials (cClinician-and pPatient-rReported SMF rRating sScales -CPRSMFRS) Point improvement in 59.2% (1 mg/cm 2 ) and 65.3% (2 mg/cm 2 ) versus 23.0% (placebo)Rzany et al (2014) NCT01294644360 ≥1-Point improvement in 58.3% (1 mg/cm 2 ) and 62.3% (2 mg/cm 2 ) versus 34.5% (placebo)Ascher et al (2014) REFINE-1 (NCT01542034) 506 ≥1-Point improvement in 70.0 versus 18.6% (placebo) REFINE-2 (NCT01546142) 516 ≥1-Point improvement in 66.5 versus 22.2% (placebo)Humphrey et al (2016) …”
mentioning
confidence: 99%